The Influence of Perceived Trust, Information Literacy and Perceived Validity on Netizens' Perception That social media is an Appropriate Instrument for The Information Deployment - Sudirjo, Frans; Nugraha, Galih; Wahyono, Teguh; Grace Putrianti, Flora; Buchori, Ahmad (Jurnal Informasi dan Teknologi, 2024)
The purpose of this study is to ascertain how information literacy, perceived validity, and perceived trust of the variables affect people's adoption of social media as a vehicle for information dissemination. In general, a quantitative method is used to conduct this research. Social media users that are active or inactive and reside in five major Indonesian cities make up the demographic used in this study. Using the purposive sampling strategy, researchers collected samples. 100 people made up the study's sample. Questionnaires were distributed as part of the data collection process. Two phases of measurement were done in this investigation by the researchers. Analyze the measurement model first, and then analyze the model structure second. According to the results, most people in five major Indonesian cities have a 70% degree of trust in information found on social media. Let us therefore suppose that 60% of the information on social media is accurate. Therefore, it can be said that most individuals have a good level of information literacy, which enables them to evaluate the veracity of the information they are given rather than blindly accepting it. Perceived validity, perceived usefulness, perceived simplicity of use, and perceived trust are all directly impacted by information literacy, and these factors will indirectly affect actual use. Through usage patterns and intentions, perceived validity influences actual use among AUs in an indirect manner. Through perceived validity, perceived trust influences actual use in an indirect manner.